EDITORIAL - Vargas, J. V. C. (Revista de Engenharia Térmica, 2008)
Petroleum will continue to play a key role in the world energetic matrix for long, in spite of the pessimistic predictions about the near shortage of the existing reserves. The offshore exploration technology in deep sea water has challenged such predictions. The recent discovery of oil in the pre-salt layer in the southern Brazilian sea coast is one of those events. The so called pre-salt layer consists of a region that develops along 800 kilometers between the Brazilian states of Espírito Santo and Santa Catarina, below the bottom of the sea, and encompasses three sedimentary basins (Espírito Santo, Campos and Santos). The oil found in this area is at depths that exceed 7 thousand meters, below a thick salt layer that geologists think that had the property of preserving oil quality. However, the oil found in deep sea water usually is heavy oil, and difficult to be refined, requiring refining advanced technologies of fluidized catalytic cracking unities (FCCU). Hence, there will be a demand for the construction and optimization of those unities in larger scale, requiring effective mathematical models and even new technologies. For example, currently Brazil is energetically independent, but exports heavy oil and imports light oil, due to the lack of the necessary number of FCCU’s for the efficient refining of heavy oil. Therefore, it is considered that the theoretical, numerical and experimental study of heavy oil refining technologies emerges as a promising line of research to be considered by thermal engineering scientists.